2023
DOI: 10.1039/d2bm00819j
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous delivery of an antibody against SARS-CoV-2 from a supramolecular hydrogel depot

Abstract: Prolonged maintenance of therapeutically-relevant levels of broadly neutralizing antibodies (bnAbs) is necessary to enable passive immunization against infectious disease.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…PNP‐1‐5 was, therefore, selected as the formulation of choice for the next steps of the study. Importantly, like previous reports, [ 12,24 ] we did not observe foreign body responses or indications of poor tolerability of PNP hydrogels, demonstrating their excellent biocompatibility (Figures S4 and S5, Supporting Information).…”
Section: Resultssupporting
confidence: 89%
“…PNP‐1‐5 was, therefore, selected as the formulation of choice for the next steps of the study. Importantly, like previous reports, [ 12,24 ] we did not observe foreign body responses or indications of poor tolerability of PNP hydrogels, demonstrating their excellent biocompatibility (Figures S4 and S5, Supporting Information).…”
Section: Resultssupporting
confidence: 89%
“…Based on all of the data described above, the L-0.9 mg 1-10 and 2-10 hydrogel formulations exhibited the most consistent and favorable pharmacokinetics, reaching steady state after just one day and maintaining stable and therapeutically relevant concentrations for the duration of the 42-day study. Yet, beyond evaluating the pharmacokinetics (PK) and pharmacodynamics (PD) of hydrogel-based GLP-1 RA therapies, simple pharmacokinetic modeling can be used to predict drug release kinetics in more clinically relevant large animals and in humans, while also aiding in the design of biomaterial depot technologies ( 41 ). Modeling can inform the optimization of the PNP hydrogel platform for delivery of cargo with similar physicochemical characteristics but different pharmacokinetic characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…As the standard clinical dosing of semaglutide for type 2 diabetes is ~1 mg weekly, we anticipated that a single administration capable of providing upwards of four months of continuous therapy must contain ~20 mg of semaglutide in a volume relevant for subcutaneous administration (e.g., generally 0.5-2 mL). We have previously reported that these injectable, biocompatible PNP hydrogel materials are capable of facile loading of diverse protein cargo at relevant concentrations with high efficiency, and enable tunable cargo delivery timeframes (32,36,(39)(40)(41)(42)(43).…”
Section: Development Of Injectable Hydrogels For Sustained Release Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our lab has previously developed a self-assembled hydrogel platform for biomedical applications including sustained delivery of physicochemically diverse therapeutic cargo. [13][14][15][16][17][18][19][20] Our efforts have focused on the development of shear-thinning and selfhealing physical hydrogels that can be easily injected and which can afford sustained delivery of multifarious vaccine cargo. [13,[21][22][23][24] Specifically, these hydrogel materials leverage strong, non-covalent polymer-nanoparticle (PNP) interactions to crosslink biopolymer chains.…”
Section: Introductionmentioning
confidence: 99%